Brain Abscess Associated with Polymicrobial Infection after Intraoral Laceration: A Pediatric Case Report - Fumihiro Ochi; Hisamichi Tauchi; Toyohisa Miyata; Tomozo Moritani; Toshiyuki Chisaka; Junpei Hamada; Kozo Nagai; Minenori Eguchi-Ishimae; Mariko Eguchi (Hindawi Limited, 2020)
Brain abscesses, infections within the brain parenchyma, can arise as complications of various conditions including infections, trauma, and surgery. However, brain abscesses due to polymicrobial organisms have rarely been reported in children. We herein report a case of a 9-year-old girl with unresolved congenital cyanotic heart disease (CCHD) presenting with right hemiplegia who was diagnosed with brain abscess caused by Streptococcus intermedius, Parvimonas micra, and Fusobacterium nucleatum after oropharyngeal injury. She was treated with intravenous antimicrobial therapy, drainage under craniotomy, and antiedema therapy with glycerol and goreisan, which led to the improvement of right hemiplegia to baseline; she was discharged following eight weeks of intravenous antimicrobial therapy. The clinical diagnosis of the brain abscess was difficult due to the nonspecific presentation, highlighting the importance of cranial imaging without haste in patients at increased risk for brain abscesses such as those with CCHD, presenting with fever in the absence of localizing symptoms or fever, accompanied with abnormal neurological findings.